PREMCHAND’S NARRATIVE VISION: AN OVERVIEW - Singh, Sanjay Kumar (International Journal of Research -GRANTHAALAYAH, 2022)
No other storyteller in Hindi, or indeed in any Indian language, has influenced the Indian people with the same depth and intimacy as Munshi Premchand. In this respect, he can only be compared to the great poet Goswami Tulsidas of the Bhakti period. Premchand’s personality and life were extremely ordinary. Premchand is the name of an ordinary-looking, quintessential Indian man of extraordinary talent, who, through his writings, captivated the hearts and minds of the people of the country. The peculiarity of his life was that there was nothing particularly special about it. His life was synonymous with pain – the pain of slavery, the pain of the country’s bondage, the pain of poverty, the pain of living without support, the pain of family misfortunes – in short, he lived a life of pain and suffering. When Premchand entered the field of writing, on one hand, the magical novels of Babu Devakinandan Khatri were all the rage in Hindi literature, while on the other hand, the romantic and detective novels of Kishorilal Goswami and Gopalram Gahmari held sway. It was a unique romantic world of kings and queens, princes and princesses, tricksters and shape-shifters, magical cellars and caves, wealth, union and separation, and the ebb and flow of emotions, which had captivated not only Hindi readers but also readers of other languages. Premchand was also influenced by this. He could have amassed immense wealth and fame by following this path. But outside this magical world, there was also a world of real, living human beings, where slavery, exploitation, hunger, poverty, illiteracy, untouchability, caste discrimination, and social evils flourished in all their glory. He voluntarily embraced this reality and struggled throughout his life to eradicate it. In the words of Dr. Nagendra, "He also worked to elevate Hindi fiction from the level of mere ’entertainment’ and connect it meaningfully with life."